Records of Inorganic Ions and Dust Particles in Snow at Yushugou Glacier No. 6 in the Desert Belt of Northwestern China - Liu, Feng; Li, Zhongqin; Hao, Jianan; Zhou, Xi; Wang, Fanglong; Zhang, Hui; Wang, Panpan; Zhang, Xin; Song, Mengyuan; Chen, Taotao (Frontiers in Earth Science, 2020)
Chemical ions and dust particles deposited in snow can be used as indicators of climatic and environmental processes. Understanding their sources, energy transfer and evolutionary mechanisms is extremely important in tracking regional climate and environmental changes. We collected snow samples from three pits at different altitudes and from the surface of Yushugou Glacier No. 6, Tianshan Mountains, China, in the summers of 2017 and 2018. Sea-salt tracing, correlation analysis and factor analysis were used to determine the characteristics and sources of the major ions and mineral dust particles in the snow. We found obvious seasonal variations, with high concentrations of dust particles and major ions deposited during the dust period, and relatively low concentrations deposited during the non-dust period. The concentrations peaked within two distinct dust layers in the snow pits. There was a significant correlation between the peak values and the dust layer. The ionic concentrations were ranked from highest to lowest as Ca2+ > SO42- > Cl- > Na+ > NO3- > NH4+ > Mg2+ > K+. Therefore, SO42- was the dominate anion and Ca2+ was the dominate cation. The major ions in the snow at Yushugou Glacier No. 6 are mainly derived from terrestrial mineral dust but also include limited inputs from human activities and sea salt.